Hot ductility of austenite stainless steel with a solidification structure - Tehovnik, Franc (Materiali in tehnologije, 2006)
A survey of the solidification structure of austenitic stainless steels is presented. The solidification occurs, depending on the content of the main alloying elements, with the primary formation of delta-ferrite or austenite. In the case of primary solidification of delta-ferrite, this phase reacts with the residual melt producing austenite with a peritectic reaction. The hot workability of the as-solidified microstructure is better in the case of primary solidification of delta-ferrite, since, in this case, the accumulation of impurities in the final melt is prevented. Some impurities, slightly soluble or insoluble in the solid phase at solidification, e.g., lead, decrease the hot workability significantly, which is also lowered in the case of the segregation of soluble impurities at the boundary of austenite and delta-ferrite. The integrity of the continuous cast slab can be improved and the cracking by hot rolling can be prevented by an optimal adiustment of the steel chemical composition and the parameters of continuous casting. Laboratory tests of one-pass rolling of wedge-shaped specimens of industrial steels have confirmed the recommendations and the conclusions in the quoted references.
Keywords: avstenitna jekla; nerjavna jekla; legirana jekla; strjevanje; mikrostruktura